Development and validation of progressive web application usability heuristics (PWAUH) - Nurfarahani, Norman Anuar; Mohd Kamal, Othman (Springer Nature, 2024)
Heuristic evaluation (HE) is widely used to evaluate various software, interfaces, systems, or application domains, but using generic heuristics will fail to detect specifc usability issues. Researchers currently rely on traditional heuristics such as Nielsen’s, SMART, SMASH, or other domain-specifc heuristics, which are unsuitable for a modern API system. Although several researchers have successfully developed heuristics specifcally for modern systems such as web apps or smartphone apps, there is a lack of specifc heuristics for Progressive Web Applications (PWA), a hybrid of native and web apps. Therefore, this paper reports the systematic development of specifc heuristics for PWA using a standard eight-step methodology: Exploratory, Experimental, Descriptive, Correlation, Selection, Specifcation, Validation, and Refnement. The PWA heuristics called PWAUH developed in this study consist of 15 heuristics. We have validated our initial PWAUH with fve experts from academia and industry, and the initial 14 heuristics are suitable for further expert validation. Subsequently, PWAUH was further validated using three diferent PWA domains, cultural heritage, stock photo industry, and marketplace, with sixteen experts ranging from academicians, UX researchers, R&D executives, and postgraduate students in HCI. An additional heuristic is included in the list in the refnement stage. Findings show that PWAUH is efective in identifying usability issues.